Spin–orbit configuration interaction study of spectral properties of PbO. (24th August 2022) - Ramirez, Gerardo; Sunga, Felizsa; Tilson, Jeffrey L; Ermler, Walter C
Abstract: Relativistic calculations of the structural and spectral properties of the PbO molecule can provide fundamental information about the importance of a proper treatment of angular momentum coupling among electrons in order to achieve accurate computational results for spectral properties. Specifically, the nature of these couplings in PbO is expected to be intermediate between the LS - and jj -coupling limits because of its light/heavy element composition. This article reports potential energy curves, transition energies, electric dipole transition moments, permanent dipole moments and spectroscopic constants of PbO calculated using a multireference single plus double excitations spin–orbit configuration interaction approach in the context of relativistic effective core potentials and their concomitant spin–orbit coupling operators. The calculated results are in general agreement with both available experimental results as well as earlier calculations. New values for properties of excited states are also reported. It is noteworthy that certain properties show larger deviations from previous calculations. These deviations are attributed to direct and indirect relativistic effects resulting from diatomic electron–electron angular momentum coupling effects, which are included consistently in the calculations reported herein.